Spatial Difference Analysis of Water Resources Carrying Capacity in Henan Province - MIAO Zhiying; FENG Yi; LIU Debo (Renmin Zhujiang)
Taking 18 cities in Henan Province as the research objects,this paper selects 16 indicators from the water resources-society-economy-ecology composite system.Utilizing the entropy weight TOPSIS method,it conducts the spatial difference analysis and comprehensive evaluation of water resources carrying capacity on 18 cities in Henan Province in 2018.The evaluation results show that the water resources carrying capacity of Henan Province in 2018 is weak.From the perspective of spatial difference,the water resources carrying capacity is the strongest in the southern region,followed by the western region,and the northern and eastern regions are the weakest.Cities with descending water resources carrying capacity are as follows: Xinyang, Zhumadian, Nanyang, Zhengzhou, Sanmenxia, Luoyang, Pingdingshan, Shangqiu, Luohe, Jiyuan, Xuchang, Zhoukou, Anyang, Kaifeng,Hebi,Xinxiang,Jiaozuo,Puyang.The water resources subsystem and the economic subsystem have great influences on water resources carrying capacity in different cities.GDP,water production modulus,and precipitation affect the water resources carrying capacity most in 2018.